Rest-activity rhythms, daytime symptoms, and functional performance among people with heart failure. (2nd August 2020) - Jeon, Sangchoon; Conley, Samantha; Redeker, Nancy S.
ABSTRACT: Sleep disturbance and decreased daytime activity are well-described among people with chronic heart failure (HF) who suffer from disabling daytime symptoms and poor function. Alterations in the circadian rhythmicity of rest-activity may also be associated with these outcomes. However, little is known about the associations between rest-activity rhythms (RARS), symptoms, and functional performance or the extent to which they are explained by sleep characteristics among people with HF. The purpose of this study is to evaluate parametric and non-parametric circadian characteristics of RARs and the associations between these variables, daytime symptoms, and functional performance among patients with stable heart failure (HF). We recruited adults with stable HF from HF disease management programs. Participants wore wrist actigraphs for 3 d, completed one night of unattended polysomnography and the Six Minute Walk Test, and reported daytime symptoms and physical function. We performed cosinor, non-parametric, and spectral analyses to evaluate the rest-activity rhythms and computed bivariate correlations between the rest-activity rhythm, demographics, daytime symptoms, and functional performance. We conducted multiple regression analysis to examine how RARs contribute to daytime symptoms and functional performance after controlling for insomnia and covariates. The sample included 135 participants [Mean age = 60.6 (16.1) y, n = 88 (65.2%) male]. Older age, greater comorbidity, and poorer New York Heart Association (NYHA) Class, and more EEG arousals were associated with greater intra-daily variability of the RAR. More robust rhythmicity represented by the circadian quotient was associated with better NYHA class and less sleep fragmentation. A higher circadian quotient was significantly associated with lower fatigue, depression, and sleepiness, and better functional performance after controlling for insomnia and clinical and demographic characteristics. Circadian parameters of rest-activity are associated with symptoms and functional performance among people with HF independent of insomnia or sleep disordered breathing. Interventions targeted at improving the stability and strength of rest-activity rhythms may improve symptom and functional outcomes for these patients.